2017
DOI: 10.1002/chem.201704538
|View full text |Cite
|
Sign up to set email alerts
|

Photomodulation of DNA‐Templated Supramolecular Assemblies

Abstract: A new type of DNA ligand that contains a phosphate-binding group and a photoresponsive azobenzene moiety is reported. When the azobenzene is in trans configuration, the ligand binds to the minor groove of a double-stranded DNA, whereas it partially desorbs upon trans-cis isomerisation with light. The ability to photoswitch the ligand upon interaction with DNA is evidenced by (chir)optical signatures, and deciphered by the differences of binding geometry, stability, and dynamics of the DNA/ligand complexes for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…We showed that the evolution of CD signals reflect the extent of ATP hydrolysis by the phosphatase, going from supramolecular polymers bound to ATP, to ADP, then AMP, and eventually phosphates. Indeed, CD signals are very sensitive to changes in the microenvironment and were shown to be effective in studying supramolecular systems, , in particular for supramolecular DNA recognition. …”
Section: Introductionmentioning
confidence: 99%
“…We showed that the evolution of CD signals reflect the extent of ATP hydrolysis by the phosphatase, going from supramolecular polymers bound to ATP, to ADP, then AMP, and eventually phosphates. Indeed, CD signals are very sensitive to changes in the microenvironment and were shown to be effective in studying supramolecular systems, , in particular for supramolecular DNA recognition. …”
Section: Introductionmentioning
confidence: 99%
“…This approach, coupled to conventional adenosine‐phosphates assays, could possibly help in the analysis of the composition in APs or other nucleotide phosphates, as recently reported for supramolecular polymers and conjugated copolymers . Moreover, the possibility of using guanidinium‐based photoresponsive molecules with GuaBiPy in multicomponent assemblies could also be exploited, for instance to modulate ATP release within dynamic supramolecular systems.…”
Section: Resultsmentioning
confidence: 99%
“…We considered one AxP molecule with a number of 4 GuaBiPy molecules as model systems to highlight the interactions at play during the self‐assembly process. To build these systems, each GuaBiPy (parameterized based on an earlier study) was oriented around a central AxP by using University of California, San Francisco Chimera software . GuaBiPy and AxP molecules were initially separated by 15 Å, according to their geometric centers, a larger distance than the cut‐off of nonbonded interactions, to avoid any bias on the recognition modes between the compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Further exploiting this prime role of π‐ stacking interactions, we have recently inserted a photoswitchable azobenzene‐based molecule, which was observed to bind to the DNA minor‐groove and was expected to influence these interactions depending on its twisted Z or coplanar E configuration. Remarkably, when interacting with ssDNA, the photoswitching of the azobenzene‐based compound allowed us to control the DNA binding of the pyrene‐based compound GuaBiPy , which is detected by its unique fluorescence signals . These results demonstrated that it is possible to achieve a photocontrol of DNA binding in heteromolecular templated assemblies, using photoswitchable ligands.…”
Section: Dna‐templated Self‐assembly Of Small Moleculesmentioning
confidence: 90%